A Sensitive High-Performance Thin Layer Chromatography Method for Simultaneous Determination of Salbutamol Sulphate and Beclomethasone Dipropionate from Inhalation Product - Nizam Patel; Vijaykumar Kunvarji Parmar (Tabriz University of Medical Sciences, 2018)
Background: A sensitive high-performance thin layer chromatographic (HPTLC) method was developed for simultaneous determination of beclomethasone dipropionate and salbutamol sulphate from inhalation product. Methods: Chromatographic separation was achieved on aluminium plates pre-coated with silica gel G60 F254 as the stationary phase and methanol:ethyl acetate:toluene:ammonia (3:1:3:0.15) as the mobile phase. The densitometric evaluation was carried out at 232 nm. The developed method was validated as per the ICH Q2 (R1) guidelines. Robustness of the proposed method was assessed using experimental design approach, and results were analyzed graphically. The results of sample analysis by proposed HPTLC method and reported HPLC method were statistically compared. Results: The Rf value of salbutamol sulphate and beclomethasone dipropionate was found to be 0.38±0.02 and 0.72±0.02, correspondingly. The response in terms of peak area was linear over the concentration range of 100-500 ng/spot and 200-1000 ng/spot for beclomethasone dipropionate and salbutamol sulphate, individually, with the regression coefficient values greater than 0.99 for both the drugs. The limit of detection and limit of quantification for beclomethasone dipropionate were found to be 27 ng/spot and 84 ng/spot, respectively and for salbutamol sulphate were 40 ng/spot and 112 ng/spot, respectively. The proposed method was found to be statistically insignificant when compared to the reported method. Conclusion: The proposed method is robust, sensitive, accurate and precise. The method can be applied for the simultaneous estimation of beclomethasone dipropionate and salbutamol sulphate from inhalation product.